DETERMINING THE USE OF CASHLESS PAYMENT METHODS AND THE CONTRIBUTING FACTORS: HOTEL GUESTS’ PERSPECTIVES IN MALAYSIA - Nur Ayu Nabila Suhaimi; Nursyawani Mat Nawi; Wan Nor Bayah Wan Kamarudin (International Journal of Accounting, Finance and Business, 2022)
Cashless systems are essential in modern life since they serve to simplify monetary transactions in an age of globalisation. People nowadays most likely choose a cashless payment method for their transactions especially in reserving hotel rooms and other charges. As the transaction can be conveniently done by using smartphones or card, it offers minimum effort. Hence, this study intends to determine the use of cashless payment among hotel guests and the contributing factors of cashless payment used. This study used convenient sampling and the screening constructs were included in the instrument to identify appropriate respondents. In total, 386 completed and usable online survey were gathered among hotel guests in Malaysia. Findings indicate debit cards are the most commonly utilised payment option for hotel guests. Positive correlation was observed between perceived ease of use, perceived usefulness, perceived security, perceived risk, and perceived enjoyment. Furthermore, when compared to other factors, perceived enjoyment was indeed the most contributing factor among hotel guests, particularly with the application of digital technologies, such as a debit card, credit card, touch-and-go e-Wallet, Grabpay, NFC and others. In conclusion, the cashless approach via electronic payment is a phenomenon among Malaysian hotel guests since it provides fast payment method through the use of technical gadgets. Recommendations and suggestions have also been made in the study for the interest of scholars.